GeoCanBlo Interactive Learning Media Implementation Assistance to Improve Spatial Skills - Putri Yulia; Ain Sri Nurhaini; Annisa Rahmawati; Isyati Radiah Putri (Sah Publisher, 2026)
Abstract. The mathematical spatial abilities of junior high school/MTsN students are often problematic; they frequently experience difficulties in visualizing and manipulating 2D and 3D objects in geometry. In addition, the use of digital media in mathematics learning is not yet optimal. Therefore, systematic assistance is needed to integrate visual, interactive, and game-based learning technologies. This community service aims to implement GeoCanBlo interactive learning media in geometry lessons to improve the mathematical spatial abilities of ninth-grade students at MTsN 5 Padang City. GeoCanBlo is an innovative learning medium that integrates Canva as a visual medium, GeoGebra as a means of dynamic geometry exploration, and Blooket games as an interactive evaluation medium for flat-sided shapes. This community service method uses the Implementation and Evaluation Method, which combines the implementation of teaching aids, student hands-on practice, and evaluation of learning products. The subjects of this community service are ninth-grade students at MTsN 5 Padang City, totaling . The research instrument is a mathematical spatial ability test that has been tested for validity and reliability. The research data was analyzed using a paired samples t-test. The results of this activity showed that there was an increase in students' mathematical spatial abilities before and after the application of the GeoCanBlo interactive learning media, as indicated by a significance value of less than 0.05. In addition, the use of GeoCanBlo media can increase student engagement in learning and help students understand spatial concepts in a more visual and interactive way. The implications of this activity show that GeoCanBlo media can be used as an alternative sustainable innovative learning model, supporting the strengthening of teachers' digital literacy, and encouraging the creation of more effective, interesting, and student-oriented mathematical learning that focuses on the development of spatial thinking skills. Keywords: GeoCanBlo, interactive, learning, media